A CASE OF INSULIN-INDUCED PERIPHERAL NEUROPATHY - Sun, CP; Yee, MC (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Insulin-induced peripheral neuropathy, known as treatment-induced diabetic neuropathy (TIDN), is an uncommon treatment-induced neuropathic pain and/or autonomic dysfunction that occurs in patients after a rapid improvement in glycaemic control. RESULTS We report a patient with underlying type 1 DM who developed TIDN after rapid improvement in glycaemic control following admission for diabetic ketoacidosis. He developed severe neuropathic pain and autonomic dysfunction manifesting as severe postural hypotension resulting in postural giddiness and unsteady gait. He was initially managed as diabetic neuropathic pain. Despite the high dosage of analgesics, pain did not improve, and postural giddiness also persisted. His HbA1C decreased from 17.5% to 7.4% in two months. The diagnosis of TIDN was made after considering the rapid reduction in HbA1c and his clinical presentation of pain and autonomic dysfunction that were not alleviated with the treatment plan for diabetic neuropathy. The patient’s insulin dosage was reduced and glycaemic targets were relaxed. Two weeks after the adjustment of medications, his condition improved tremendously. CONCLUSION Insulin-induced peripheral neuropathy or TIDN is arare condition. It is often misdiagnosed as other types of neuropathy, as TIDN presents similarly with diabetic peripheral neuropathy and many physicians may not be aware of this condition. The diagnosis of TIDN must be kept in mind when patients on high doses of antidiabetic agents present with severe neuropathic pain with or without autonomic dysfunction. This may be prevented by administering less aggressive therapy for sugar control.